A Safety Collision Avoidance Algorithm Based on Comprehensive Characteristics. (17th March 2020) - Zhang, Y. J.; Du, F.; Wang, J.; Ke, L. S.; Wang, M.; Hu, Y.; Yu, M.; Li, G. H.; Zhan, A. Y.
Abstract : Aiming at the requirements of vehicle safety collision avoidance system, a safety collision avoidance algorithm based on environmental characteristics and driver characteristics is proposed. By analyzing the relationship between collision avoidance time and the environment, a safety time model is established. In the established safety time model, parameters based on driver characteristics are added, which increases the flexibility of the algorithm. The algorithm can adapt to more different driving conditions and give appropriate warning thresholds. After simulation and comparison with other algorithms, the algorithm proposed in this paper can satisfied the requirements of reducing vehicle collision risk. The effectiveness and feasibility of the algorithm are verified, and the safety of vehicle driving can be improved.